2010
DOI: 10.1088/0957-0233/22/1/015201
|View full text |Cite
|
Sign up to set email alerts
|

Increasing sensitivity of arc-induced long-period gratings—pushing the fabrication technique toward its limits

Abstract: This paper presents an investigation of the sensing properties of long-period gratings (LPGs) written with the electric-arc technique in commonly used standard germanium-doped Corning SMF28 and boron co-doped Fibercore PS1250/1500 fibers. In order to increase the sensitivity of the LPGs, we studied and established for each fiber the writing parameters allowing for the coupling of the highest possible order of cladding modes at a resonance wavelength around λ = 1550 nm. The sensitivity of the LPGs to refractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 16 publications
2
58
0
1
Order By: Relevance
“…Fabrication procedure of LPGs with computer-assisted precision arc-discharge apparatus has been described previously in [15]. In this stage of the experiment, we used Corning SMF28 fiber samples to write gratings with period of Λ = 500 µm.…”
Section: Methodsmentioning
confidence: 99%
“…Fabrication procedure of LPGs with computer-assisted precision arc-discharge apparatus has been described previously in [15]. In this stage of the experiment, we used Corning SMF28 fiber samples to write gratings with period of Λ = 500 µm.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous works we have reported the significant sensitivity of LPGs written with a cost-effective electric arc method in standard germanium-containing single-mode fiber (Corning SMF28) 5 , pure fused silica endless single-mode photonic crystal fiber (PCF ESM-12-01) 6 and germanium and boron (B/Ge) co-doped photosensitive fiber (Fibercore PS 1250/1500) 7 . The sensitivity of the structures was as high as 13 and 220 pm/bar for the SMF28 and PS 1250/1500 fibers, respectively 8 . The LPGs written in boron co-doped fiber show the highest pressure sensitivity reported to date in the literature.…”
Section: Introductionmentioning
confidence: 93%
“…The main limitation of the EAD-based technique is the difficulty in the fabrication of grating with low pitch. In 2011, Smietana et al reported on the fabrication of a LPG in SMF28 fiber with period of 345 µm, whereas a grating with period of 221 µm was demonstrated in an unconventional fiber (boron co-doped fiber, which is more sensitive to the temperature generated by the arc than the standard fiber) [34]. More recently, the same group demonstrated that LPGs with period lower than 200 μm could be realized only in boron co-doped fibers and with a grating length greater than 50 mm [35].…”
Section: Introductionmentioning
confidence: 99%